Radiomic analysis of the proximal femur in osteoporosis women using 3T MRI - Martel, Dimitri; Monga, Anmol; Chang, Gregory (Frontiers in Radiology, 2023)
Introduction: Osteoporosis (OP) results in weak bone and can ultimately lead to fracture. MRI assessment of bone structure and microarchitecture has been proposed as method to assess bone quality and fracture risk in vivo. Radiomics provides a framework to analyze the textural information of MR images. The purpose of this study was to analyze the radiomic features and its ability to differentiate between subjects with and without prior fragility fracture. Methods: MRI acquisition was performed on n= 45 female OP subjects: 15 with fracture history (Fx) and 30 without fracture history (nFx) using a high-resolution 3D Fast Low Angle Shot (FLASH) sequence at 3T. Second and first order radiomic features were calculated in the trabecular region of the proximal femur on T1-weighted MRI signal of a matched dataset. Significance of the feature’s predictive ability was measured using Wilcoxon test and Area Under the ROC (AUROC) curve analysis. The features were correlated DXA and FRAX score. Result: A set of three independent radiomic features (Dependence Non-Uniformity (DNU), Low Gray Level Emphasis (LGLE) and Kurtosis) showed significant ability to predict fragility fracture (AUROC DNU = 0.751, p<0.05; AUROC LGLE = 0.729, p<0.05; AUROC Kurtosis =0.718, p<0.05) with low to moderate correlation with FRAX and DXA.) . Conclusion: Radiomic features can measure bone health in MRI of proximal femur and has the potential to predict fracture.